Application of a voltage compensation type active superconducting current controller to current limiting capability of power grid. (October 2018) - Shi, Jing; Zhang, Lihui; Zhou, Xiao; Li, Yuanyuan; Su, Rongyu; Ren, Li; Li, Jingdong; Tang, Yuejin
Highlights: The suggested SCC's performance is assessed in a single-phase power system. Compared to conventional or superconducting iron core transformers, the superconducting air-core transformer has many advantages: I. No iron loss; II. No magnetic saturation; III. No surge; IV. No resonance; V. The transformer design scheme is flexible, etc. The suggested SCC can reduce the influence of fault current on power system in a certain extent, and improve the security and economics of power system. A series of experiments are carried out in the laboratory to evaluate the dynamic characteristic of the SCC. The suggested SCC can respond to the system power requirement quickly and accurately; the SCC can regulate the amplitude and phase of the series compensation voltage effectively. Abstract: This paper introduces a laboratory prototype of 800 V/30 A active superconducting current controller (SCC). The SCC has three main components, a series connected superconducting transformer, a controllable compensation voltage source, and a supercapacitor energy storage unit. To solve the issue of transformer magnetic saturation, an air-core superconducting transformer is adopted. The controllable compensation voltage source is composed of voltage source PWM converter and DC chopper, which control the amplitude and phase of the output voltage of SCC. The supercapacitor module is adopted to compensate the dynamic power during current control process. To evaluate the dynamic characteristic of the SCC, a series of experiments are carried out in the laboratory. With the energy storage support, the SCC can control the current level quickly and effectively, which can cooperate with the action of circuit breaker.